Drawing the future: gender and future occupational aspirations of young children in Sweden - Wamala-Andersson, Sarah; Richardson, Matt X.; Schölin Bywall, Karin; Norgren, Therese; Chambers, Nick (Frontiers in Education, 2025)
IntroductionResearch on young children’s occupational aspirations and the factors shaping them is still limited, especially in early interventions addressing gender disparities in high-status fields like STEM.MethodsThis is the first study in Sweden utilizing the Drawing the Future method, surveyed 1,832 children (aged 5–13) from 28 schools in Skåne region of southern, asking them to draw their dream jobs. This exercise was conducted in a classroom setting and facilitated by their class teacher.ResultsSignificant gender differences emerged, revealing distinct stereotypical patterns in children’s future occupational aspirations and influencing factors. Only three occupations—footballer, doctor, and police officer—were popular among both genders. Girls preferred people- or animal-centered roles, while boys leaned toward jobs involving “things” (p < 0.001). Girls felt they could pursue similar careers as boys, but boys showed more skepticism (p < 0.001). Influence patterns also varied by gender: 25% of girls were inspired by mothers, while 45% of boys were inspired by fathers (p = 0.02). Beyond immediate family, girls often sought career information from acquaintances, while boys turned to media (p < 0.001). STEM interest was limited, with “game developer” being the only STEM job on boys’ lists. Additionally, a larger proportion of boys ranked STEM subjects among their top 10 favorite school subjects, while girls preferred crafts, art, and English (p < 0.001).DiscussionThese findings highlight the need for early, unbiased, evidence-based career interventions and policies to broaden children’s awareness of diverse job options and opportunities in the labor market.